BaGdF5:Dy3+, Tb3+, Eu3+ multifunctional nanospheres: paramagnetic, luminescence, energy transfer, and tunable color. Issue 20 (5th May 2016) - Guan, Hongxia; Song, Yanhua; Zheng, Keyan; Sheng, Ye; Zou, Haifeng
Abstract : The photoluminescence emission color tones of BaGdF5 :Dy 3+, Tb 3+, Eu 3+ nanomaterials change from yellow-green to red by adjusting the doping concentration and the different excitation wavelengths. Furthermore, the obtained samples also exhibit paramagnetic properties. Abstract : A series of Dy 3+, Tb 3+ and Eu 3+ singly, doubly or triply doped BaGdF5 phosphors were synthesized by a one-step hydrothermal method withl -arginine, and their energy transfer, migrations and multicolored luminescence properties were investigated in detail. The as-prepared Dy 3+, Tb 3+ or Eu 3+ doped samples showed strong blue, green and red emission, respectively. Different hues of green and red light were obtained by co-doped Dy 3+, Tb 3+ and Tb 3+, Eu 3+ in the BaGdF5 host, respectively. More significantly, in the Dy 3+, Tb 3+, Eu 3+ tri-doped BaGdF5 phosphors, colors changed from yellow green to orange red by adjusting the doping concentration of Eu 3+ . Energy migrations from Dy 3+ to Tb 3+ and from Tb 3+ to Eu 3+ are reported in detail. Furthermore, the obtained samples exhibit paramagnetic properties at room temperature and low temperature. It is obvious that these Dy 3+, Tb 3+, Eu 3+ singly or doubly or triply doped BaGdF5 nanomaterials with tunable multicolored luminescence properties may have potential applications in the fields of full-color displays, biological labels and bio-separation.